Endoplasmic Reticulum Stress Is Involved in Stress-Induced Hypothalamic Neuronal Injury in Rats via the PERK-ATF4-CHOP and IRE1-ASK1-JNK Pathways - Yi, Shanyong; Chen, Ke; Zhang, Lihua; Shi, Weibo; Zhang, Yaxing; Niu, Shiba; Jia, Miaomiao; Cong, Bin; Li, Yingmin (Frontiers in Cellular Neuroscience, 2019)
Objective: As a high-level nerve center that regulates visceral and endocrine activity, the hypothalamus plays an important role in regulating the body’s stress response. Previous studies have shown that stress can cause damage to hypothalamic neurons. The present study aimed to further clarify the mechanism of endoplasmic reticulum stress involvement in hypothalamic neuronal injury. Methods: A 7-day stressed rat model was established with daily restraining for 8 h and forced ice-water swimming for 5 min. The rats were randomly divided into control, stress, stress + GSK2606414 (PERK phosphorylation inhibitor), stress + KIRA6 (IRE1 phosphokinase activity inhibitor), GSK2606414 and KIRA6 groups. The pathological changes of hypothalamic neurons were observed by thionine staining. Expression of endoplasmic reticulum stress proteins GRP78, ATF4, ASK1, JNK and CHOP in the hypothalamic neurons were observed by immunohistochemical staining. The expression of JNK and CHOP mRNA in the hypothalamic neurons were observed by RNA in situ hybridization (RNA Scope), and the expression of related proteins and mRNA was semiquantitatively analyzed by microscopy-based multicolor tissue cytometry (MMTC). Results: Thionine staining revealed that stress exposure resulted in edema, a lack of Nissl bodies, and pyknosis in hypothalamic neurons. Immunohistochemistry and RNA Scope showed that stress exposure significantly increased the expression of GRP78, ATF4, ASK1, CHOP, JNK, JNK mRNA and CHOP mRNA. Treatment with PERK and IRE1 inhibitors attenuated pathological damage and downregulated the expression of ATF4, ASK1, JNK, CHOP, JNK mRNA and CHOP mRNA. Conclusion: Stress caused pathological changes in rat hypothalamic neurons. Endoplasmic reticulum stress PERK-ATF4-CHOP and IRE1-ASK1-JNK pathways were involved in the injury process.